2005
DOI: 10.2527/2005.83112663x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplementation of whole corn germ on reproductive performance, calf performance, and leptin concentration in primiparous and mature beef cows1

Abstract: A 2-yr study using primiparous and multiparous, spring-calving, crossbred beef cows was conducted to evaluate the effects of supplemental whole corn germ on reproductive performance, calf performance, and serum leptin concentrations. Each year, cows were blocked by age and BCS and assigned randomly to one of three treatments: PRE (n = 115) cows received 1.14 kg/d (DM basis) of whole corn germ for approximately 45 d before calving; POST (n = 109) cows were fed 1.14 kg/d of whole corn germ for approximately 45 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…In agreement, Small et al (2004) showed no associated effects from limit-fed, high-fat diets offered for 61 d precalving on postpartum BW and BCS through breeding compared with isoenergetic, isonitrogenous control diets. Other reports support the absence of an effect of prepartum supplemental lipids on BW and BCS change during the postpartum period (Alexander et al, 2001;Martin et al, 2005).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In agreement, Small et al (2004) showed no associated effects from limit-fed, high-fat diets offered for 61 d precalving on postpartum BW and BCS through breeding compared with isoenergetic, isonitrogenous control diets. Other reports support the absence of an effect of prepartum supplemental lipids on BW and BCS change during the postpartum period (Alexander et al, 2001;Martin et al, 2005).…”
Section: Discussionmentioning
confidence: 86%
“…Calves from DDGS-supplemented heifers had similar birth weights, weaning weights, and ADG compared with calves from SBH-supplemented heifers in the present study. Similarly, Martin et al (2005) reported corn germ supplementation during the prepartum period did not influence calf birth or weaning weights, and Small et al (2004) reported similar calf birth weights, weaning weights and ADG for limit-fed gestation diets with or without fat. Miner et al (1990) reported calf birth weights to be similar between dams fed soybean meal diets with or without additional UIP or fat.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Some researchers also reported that there are linear relationships between circulating leptin and body condition score (BCS) in cows, though the correlation coefficient was low (Lents et al . 2005; Martin et al . 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Least squares means were compared using the PDIFF option of SAS. Percentage of heifers reaching puberty, estrus synchronization response, conception rate, and pregnancy rates were analyzed after logit transformation using PROC MIXED as previously described (Cox, 1988;Martin et al, 2005). Technician and service sire were included in the initial model for AI conception and pregnancy rates but were removed from the final model because they were not significant.…”
Section: Discussionmentioning
confidence: 99%